Responding to the Paris attack : beware the fatal error - Farish A. Noor (2015)
The killings in Paris have resulted in panic and public concern, but the authories should not give the attackers what they seek. States and security forces should avoid the trap of reacting to terrorist violence with overwhelming state violence, which would serve the interests of radical militant froups to sow distrust and antagonism.